Polyspecific, antiviral immune response distinguishes multiple sclerosis and neuromyelitis optica. Issue 10 (12th February 2008) - Jarius, S; Franciotta, D; Bergamaschi, R; Rauer, S; Wandinger, K P; Petereit, H F; Maurer, M; Tumani, H; Vincent, A; Eichhorn, P; Wildemann, B; Wick, M; et al.
Abstract : Background: A polyspecific, intrathecal humoral immune response against neurotropic viruses such as measles, rubella and varicella zoster virus (MRZ reaction, MRZR) is present in 80–100% of patients with multiple sclerosis (MS), but has not to date been evaluated in patients with neuromyelitis optica (NMO). Aims: To evaluate whether MRZR distinguishes NMO and MS. Methods: 20 patients with NMO and 42 with MS were included. The intrathecal synthesis of antibodies against measles, rubella and varicella zoster virus was detected by calculation of the respective antibody indices (AI). Results: A positive MRZ reaction, as defined by a combination of at least two positive AIs, was found in 37/42 MS, but in only 1/20 NMO patients (p<0.0001). Median AI values differed significantly between the groups (p<0.0005). Conclusions: The polyspecific antiviral humoral immune response characteristic for MS is widely missing in NMO, irrespective of the NMO-IgG status of the patients. Our findings further strengthen the case for NMO being pathologically distinct from MS.